Evaluating recruitment strategies for AUSPICE, a large Australian community‐based randomised controlled trial. Issue 9 (25th March 2019) - Peel, Roseanne; Ren, Shu; Hure, Alexis; Evans, Tiffany‐Jane; D'Este, Catherine A; Abhayaratna, Walter P; Tonkin, Andrew M; Hopper, Ingrid; Thrift, Amanda G; Levi, Christopher R; Sturm, Jonathan; Durrheim, David; et al.
Abstract: Objectives: To examine the effectiveness of different strategies for recruiting participants for a large Australian randomised controlled trial (RCT), the Australian Study for the Prevention through Immunisation of Cardiovascular Events (AUSPICE). Design, setting, participants: Men and women aged 55–60 years with at least two cardiovascular risk factors (hypertension, hypercholesterolaemia, overweight/obesity) were recruited for a multicentre placebo‐controlled RCT assessing the effectiveness of 23‐valent pneumococcal polysaccharide vaccine (23vPPV) for preventing cardiovascular events. Methods: Invitations were mailed by the Australian Department of Human Services to people in the Medicare database aged 55–60 years; reminders were sent 2 weeks later. Invitees could respond in hard copy or electronically. Direct recruitment was supplemented by asking invitees to extend the invitation to friends and family (snowball sampling) and by Facebook advertising. Main outcome: Proportions of invitees completing screening questionnaire and recruited for participation in the RCT. Results: 21 526 of 154 992 invited people (14%) responded by completing the screening questionnaire, of whom 4725 people were eligible and recruited for the study. Despite the minimal study burden (one questionnaire, one clinic visit), the overall participation rate was 3%, or an estimated 10% of eligible persons. Only 16% of eventual participants had responded within 2 weeks of the initial invitation letter (early responders); early and late responders did not differ in their demographic or medical characteristics. Socio‐economic disadvantage did not markedly influence response rates. Facebook advertising and snowball sampling did not increase recruitment. Conclusions: Trial participation rates are low, and multiple concurrent methods are needed to maximise recruitment. Social media strategies may not be successful in older age groups. Trial registration: Australian New Zealand Clinical Trials Registry, ACTRN12615000536561.